2005
DOI: 10.1007/s10750-004-3370-0
|View full text |Cite
|
Sign up to set email alerts
|

Stable carbon isotope ratios for the gray whale (Eschrichtius robustus) in the breeding grounds of Baja California Sur, Mexico

Abstract: This work investigated the feeding ecology and behaviour of gray whales in Bahı´a Magdalena. Underwater observations of bottom feeding were made (n ¼ 4). Skin biopsies of the gray whale had a carbon isotope value of )16.5 ± 0.1& (range from )16.4 to )16.7, n ¼ 7). Prey in Bahı´a Magdalena had a carbon isotope value of )18.4&. Dietary enrichment from prey in Bahı´a Magdalena would correspond to 2 ± 0.1&, whereas previously published results for prey in Alaska would result in an enrichment of 3&, which suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…Stable-carbon isotope values of the diet calculated for point C (i.e. close to the death date) showed that most of the whales had values close to -18.4&, which matches that of the amphipod prey for the gray whale (mostly Ericthonius brasiliensis) in Bahía Magdalena (Caraveo-Patiñ o & Soto, 2005). Quite possibly then, most of these whales fed on prey from areas close to the wintering lagoon prior to their death.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Stable-carbon isotope values of the diet calculated for point C (i.e. close to the death date) showed that most of the whales had values close to -18.4&, which matches that of the amphipod prey for the gray whale (mostly Ericthonius brasiliensis) in Bahía Magdalena (Caraveo-Patiñ o & Soto, 2005). Quite possibly then, most of these whales fed on prey from areas close to the wintering lagoon prior to their death.…”
Section: Discussionmentioning
confidence: 60%
“…From the plates collected in Bahía Magdalena, GW51 was extracted from an individual probably death during January of 2000, with a body length of~8 m; GW31 and GW32 were extracted from adult gray whales, but their body lengths and their probable death date were unknown; GW00 was the same plate of a yearling animal previously analyzed for d 13 C only by Caraveo-Patiñ o & Soto (2005), which was collected during the wintering season in 2000, its probable death date was January also. The other two plates (GW11and GW12) found in Laguna Ojo de Liebre, these were collected from adult whales (>9.5 m) during the wintering season in 2002, their probably death data was between March and April.…”
Section: Field Samplingmentioning
confidence: 99%
See 3 more Smart Citations